Test the potensial use of Trichoderma harzianum Rifai and Gliocladium virens Arx fungi to control leaf spot disease in cayenne pepper (Capsicum frutescens L.) - sopialena sopialena (Jurnal Agroekoteknologi Tropika Lembab, 2018)
This study aims to determine the effect of effective administration and dose of antagonistic fungus Trichoderma harzianum and Gliocladium virens that can suppress the intensity of disease attacks. So this indirectly has an effect to increase yield on cayenne pepper (Capsicum frutescens L.). This research is done about 4 months from May until August 2017 starting from preparation of research of Harvest. This research was conducted at Jl. Struggle 9 Village South Sempaja, North Samarinda District, Samarinda City and the Laboratory of Plant Disease Pest Faculty of Agriculture Mulawarman University. This study used Competely Randomized Design (CRD) consisting of six treatments and five replications. Without treatment (p0), Trichoderma harzianum with a dose of 24 g (p1), Gliocladium virens at a dose of 24 g (p2), 6 g T. harzianum + 18 g G. virens (p3), 12 g T. harzianum + 12 g G virens (p4), 18 g T. harzianum + 6 g G. virens (p5). The results showed that treatment of p1 with a dose of 24 grams Trichoderma harzianum able to suppress the intensity of disease attacks up to 17.08%. Treatment p2 with a dose of 24 grams Gliocladium virens is able to increase fruit weight to 19.95 grams.